English Communication Skill Used by Indonesian Seafarer on Radio Communication - Haryani Haryani; Januarius Mujiyanto; Rudi Hartono; Issy Yuliasri (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This study aims to identify the graduates’ perspectives on the usage of English as communication on board vessels, between ship to ship or ship to shore. The identification was made by investigating the maritime institution graduates or maritime alumni perspectives which focused on the language terms of using the English language through radio communication. This research adopted a qualitative approach with descriptive analysis to investigate the language elements. The study sample consisted of 8 Nautical Graduate Students from three Maritime Institutions in Indonesia who had been working at an ocean-going vessel for 2 years or more. The data were collected and generated from their perspective answers on the questionnaires and also from radio communication transcripts. The results showed that the communication that happened on board vessels which were done by the deck department was successful enough but still less in using language components such as good grammar and correct pronunciation. Then, the English language user or skillful communicator must know how to send the message well in order to avoid miscommunication and should consider the English competence in order to avoid accidents and incidents at sea.